1992
DOI: 10.1073/pnas.89.17.7949
|View full text |Cite
|
Sign up to set email alerts
|

Murine serum amyloid A3 is a high density apolipoprotein and is secreted by macrophages.

Abstract: The serum amyloid A (SAA) proteins make up a multigene family of apolipoproteins associated with high density lipoproteins. They are of ancient origin; the filnding of a highly homologous protein in mammals and ducks indicates that SAAs have been in existence for at least 300 million years. The interspecies similarity among the SAAs makes the mouse, in which they have been most thoroughly studied, a reasonable model to use for defining the function(s) of this family of proteins in humans. Originally it was obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
105
2
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(116 citation statements)
references
References 32 publications
8
105
2
1
Order By: Relevance
“…4 *-49 SAA3, on the other hand, appears to be expressed primarily by tissue macrophages. 50 Our findings contrast with a previous study in which heart tissue of casein-treated mice failed to accumulate significant SAA proteins. 46 The explanation for this may be due in part to the fact that casein treatment induces an acute inflammatory response, whereas autoimmune disease in MRLJlpr mice results in chronic inflammation.…”
contrasting
confidence: 57%
See 1 more Smart Citation
“…4 *-49 SAA3, on the other hand, appears to be expressed primarily by tissue macrophages. 50 Our findings contrast with a previous study in which heart tissue of casein-treated mice failed to accumulate significant SAA proteins. 46 The explanation for this may be due in part to the fact that casein treatment induces an acute inflammatory response, whereas autoimmune disease in MRLJlpr mice results in chronic inflammation.…”
contrasting
confidence: 57%
“…SAA3, on the other hand, appears to be produced primarily by macrophages. 50 Using monospecific, polyclonal antisera to SAA1, SAA2, and SAA3 proteins, we observed intense positive staining in the intercellular space, capillaries, and cellular infiltrations in the myocardium of MRLJlpr mice fed the atherogenic diet ( Figures 5B and 5D). Coronary arteries that had vasculitis showed some positive staining in the intima and in cellular infiltrates.…”
Section: Immunohistochemical Studiesmentioning
confidence: 96%
“…SAA is encoded by a family of genes in many animals [5,6] including man [7] and rabbit [8]. Several studies of the biosynthesis of SAA have identified the hepatocyte as the primary source of this protein [9], but expression of SAA in other cells is also found [10].…”
Section: Introductionmentioning
confidence: 99%
“…Proinflammatory stimuli induce SAA expression in liver; optimal expression is achieved with a combination of interleukin (IL)-1 and IL-6 (10,11). Extrahepatic synthesis of SAA by synovial fibroblasts, macrophages, adipocytes, and smooth muscle cells has been documented (12)(13)(14)(15). SAA is also expressed in atherosclerotic lesions (13,16,17).…”
mentioning
confidence: 99%